An astronomically calibrated stratigraphy of the Cenomanian, Turonian and earliest Coniacian from the Cretaceous Western Interior Seaway, USA: Implications for global chronostratigraphy. (September 2015) - Eldrett, James S.; Ma, Chao; Bergman, Steven C.; Lutz, Brendan; Gregory, F. John; Dodsworth, Paul; Phipps, Mark; Hardas, Petros; Minisini, Daniel; Ozkan, Aysen; Ramezani, Jahander; Bowring, Samuel A.; et al.
Abstract: This study describes integrated, astronomically tuned age models for a relatively expanded section of the Eagle Ford Group (Texas, USA) from the Shell Iona-1 research core, which encompass >8 Myr ranging from the earliest Cenomanian to the earliest Coniacian. Biostratigraphy combined with U–Pb dates from individual zircons representing ten bentonites provide geochronologic constraints for the astronomical analyses. The astronomically tuned age models were used to calibrate a full suite of regional and globally recognized age diagnostic biostratigraphic (integrated micropaleontological, nannopaleontological and palynological analyses), geochemical, as well as isotopic events. Newly developed integrated astronomical age models provide two estimates for the Cenomanian-Turonian boundary age of 94.10 ± 0.13 Ma and 94.07 ± 0.16 Ma similar to that previously proposed from the Cretaceous Western Interior Seaway. The duration of Oceanic Anoxic Event-2 (OAE-2) was calcuated as 0.71 ± 0.17 Myr, consistent with other records from the KWIS, and several globally correlatetable, precursor events prior to the main CIE have been identified. Elsewhere in North America, the middle-upper Turonian strata are generally missing due to a hiatus, whereas the new data indicate it is relatively intact in the Iona-1 core, and thus provides a critical record to fill this gap in our understanding. As such, the Iona-1 core is one of the most complete and best-preserved records of the Cenomanian, Turonian and early Coniacian stages, and therefore provides insights into Late Cretaceous paleoclimate and paleoenvironment during this critical period in Earth history. Highlights: Astronomic age model for the Cenomanian, Turonian and earliest Coniacian. Calibrated age diagnostic biostratigraphic, geochronologic and isotopic events. Provide high-precision independent age control for regional and global correlation. Cenomanian-Turonian Boundary age calibrated as 94.10 ± 0.13 Ma. Constrained the duration of OAE-2 to 0.71 ± 0.17 Myrs.